2015
DOI: 10.1007/s40475-015-0047-x
|View full text |Cite
|
Sign up to set email alerts
|

The Lung Immune Niche in Tuberculosis: Insights from Studies on Human Alveolar Macrophages

Abstract: Tuberculosis (TB) is a disease that continues to cause global mortality and morbidity. Transmission of Mycobacterium tuberculosis (Mtb) occurs by aerosol transmission from an infected case, making the lung the primary portal of entry for the bacterium. Alveolar macrophages are the frontline cells involved in the control of subsequent replication and spread of disease. Although animal models have provided important information in the field of macrophage immunology and cell biology, human TB disease has several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Such a suggestion has been made based on the variability in the interaction of the Mycobacterium tuberculosis inside the immune system. Likewise, previous studies indicated that the Mycobacterium tuberculosis has often interacted with many types of cytokines to infect the lungs of its host [67,73,74]. Thus, the interaction of Mycobacterium tuberculosis has involved several types of cytokines while causing TB within the lungs of an infected person or animal.…”
Section: Diagnosis Of Tuberculosismentioning
confidence: 98%
See 2 more Smart Citations
“…Such a suggestion has been made based on the variability in the interaction of the Mycobacterium tuberculosis inside the immune system. Likewise, previous studies indicated that the Mycobacterium tuberculosis has often interacted with many types of cytokines to infect the lungs of its host [67,73,74]. Thus, the interaction of Mycobacterium tuberculosis has involved several types of cytokines while causing TB within the lungs of an infected person or animal.…”
Section: Diagnosis Of Tuberculosismentioning
confidence: 98%
“…The Mycobacterium tuberculosis agent has disabled the alveolar macrophage to infect the lungs of its host. Research indicated that the macrophage is an antigen that has engulfed or killed the foreign particles attempting to invade the immune system of a host [67,68,59]. However, in many instances, the Mycobacterium tuberculosis species has been observed in inhibiting the function of T-lymphocytes and immune response of the alveolar macrophages to survive within a TB-infected person or animal [68,69,59].…”
Section: Literature Review Epidemiology Of Tuberculosismentioning
confidence: 99%
See 1 more Smart Citation
“…Human alveolar macrophages are the frontline cells controlling TB's subsequent replication and spread of infection. Therefore, understanding the alveolar macrophage biology as an immune response and their interactions with M.tb is essential for understanding how to address TB control at various stages of the disease and developing better future vaccination and drug strategies [88] .…”
Section: Genetic Polymorphism In Tb Patientsmentioning
confidence: 99%